Utilidad clínica de tratamientos con ozonoterapia en patologías bucodentales - Erick Alexander, Pantoja Trávez (2022)
Abstrac The purpose of this research was focused on determining the clinical utility of ozone therapy in oral pathologies, with the general objective of evaluating its effectiveness through reports in the literature. The study was carried out through a review of several scientific articles from the last 10 years, by collecting publications in relevant scientific databases; with a total of 84 articles for the systematic review process. The analysis of the scientific documents showed evidence of the effectiveness of ozone in 90% of the total cases analyzed, being able to determine that it is a highly viable alternative to obtain favorable results as an individual treatment or as an adjunct to conventional treatments of oral pathologies, this due to to all its properties and mechanisms of action that cause positive effects on the body, likewise it should be noted that there are certain toxic properties for which its application is controversial throughout the dental field. The applications of ozone therapy in dentistry are considered a viable alternative mainly in areas such as periodontics and implantology, endodontics, cariology, pediatric dentistry, temporomandibular disorders, surgery, oral pathology and orthodontics. The lack of standardization of the protocols related to each application of ozone therapy in dental treatments, in addition to the high cost of an ozone generator, were recognized as limitations. Finally, it is proposed to students and professionals in dentistry to expand their theoretical and practical knowledge on the subject for its proper use with a good clinical result and without complications. Keywords: ozone therapy, oral pathologies, dentistry.